South Asia Regional Office (SAO) - International Food Policy Research Institute (2013)
IFPRI launched its South Asia Initiative in 2002 and established its South Asia Office (SAO) in New Delhi in 2005. SAO engages in evidence-based research and capacity strengthening related to food and nutrition security in the region.